METHOD OF AN ESTIMATION OF INFLUENCE ANISOTROPIC IRREGULARITIES IN AN IONOSPHERE ON CHARACTERISTICS OF THE CHANNEL OF A SATELLITE COMMUNICATION - Vyacheslav Anatolievich Shevchenko (Вестник Северо-Кавказского федерального университета, 2022)
In the article action of the anisotropic irregularities in an ionosphere on a satellite channel is investi- gated. Relations between the exponent, characterising depth of fadings in a communication channel, with sta- tistical performances of the aniisotropic irregularities in an ionosphere are spotted.